Dinamika konflik Papua dan kesenjangan pembangunan antar wilayah: Analisis geopolitik dan geostrategi dalam kerangka ketahanan - Auliya, Tasya (Maliki Interdisciplinary Journal, 2026)
The phenomenon of conflict in Papua and the dynamics of development tend to be Java-centric. The results of the study show that Indonesia’s complex geographical conditions characterized by remote and hard-to-reach areas are often used by separatist groups to weaken state control. On the other hand, development inequality between regions has the potential to cause dissatisfaction that can develop into horizontal or vertical conflicts. in perspective and geopolitics and geostrategy within the framework of Indonesia’s national resilience system, especially in dealing with geopolitical-based internal conflicts such as separatist movements and development gaps between regions. Conceptually, Indonesia’s geopolitics is rooted in the Nusantara Insight which places regional unity as a single political, economic, social, and security defense entity. Meanwhile, geostrategy is realized through state policies and operational steps in maintaining national stability and integration.